Tilting deformation analysis and instability prediction of arch-locked-segment landslides induced by rainfall - Jingjing Liu; Handong Liu; Jiaming Luo; Jiaxing Chen; Hu Wang (Scientific Reports)
Abstract The failure of locked-segment landslides is associated with the destruction of locked segments that exhibit an energy accumulation effect. Thus, understanding their failure mode and instability mechanism for landslide hazard prevention and control is critical. In this paper, multiple instruments, such as tilt sensors, pore water pressure gauges, moisture sensors, matrix suction sensors, resistance strain gauges, miniature earth pressure sensors, a three-dimensional (3D) laser scanner, and a camera, were used to conduct the physical model tests on the rainfall-induced arch locked-segment landslide to analyze the resulting tilting deformation and evolution mechanism. The results indicate that the tilting deformation characteristics in the locked segment are consistent with the variation in its strain, stress, hydrodynamic responses, and slope morphology, suggesting that tilting deformation can serve as a novel monitoring approach for landslide instability. Further, the tangent angle method and the tilting rate reciprocal method can be utilized to predict the landslide instability based on the landslide tilting deformation curve. The effectiveness of this method is validated in the Huangzangsi dam area, which provides theoretical foundations for understanding the catastrophic mechanism and instability prediction of arch-locked-segment landslides.